2005
DOI: 10.1161/01.cir.0000151290.04952.3b
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning Inhibits Mitochondrial Permeability Transition

Abstract: Background-Brief periods of ischemia performed just at the time of reperfusion can reduce infarct size, a phenomenon called "postconditioning." After reflow, opening of the mitochondrial permeability transition pore (mPTP) has been involved in lethal reperfusion injury. We hypothesized that postconditioning may modulate mPTP opening. Methods and Results-Anesthetized open-chest rabbits underwent 30 minutes of ischemia and 4 hours of reperfusion.Control hearts underwent no additional intervention. Postconditioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
316
1
23

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(366 citation statements)
references
References 28 publications
21
316
1
23
Order By: Relevance
“…24 It has become increasing clear that prevention of mPTP opening plays a critical role as an end-effector in myocardial protection against ischemia-reperfusion injury. [25][26][27][28][29] Whether isoflurane inhibits mPTP by attenuating glycogen synthase kinase-3β activity through Erk1/2-p70s6K signaling is presently unknown. This hypothesis is being actively investigated by our laboratory, and certainly appears to be very plausible based on recent findings indicating that desflurane-induced preconditioning is mediated by inhibition of mitochondrial permeability transition.…”
Section: Discussionmentioning
confidence: 99%
“…24 It has become increasing clear that prevention of mPTP opening plays a critical role as an end-effector in myocardial protection against ischemia-reperfusion injury. [25][26][27][28][29] Whether isoflurane inhibits mPTP by attenuating glycogen synthase kinase-3β activity through Erk1/2-p70s6K signaling is presently unknown. This hypothesis is being actively investigated by our laboratory, and certainly appears to be very plausible based on recent findings indicating that desflurane-induced preconditioning is mediated by inhibition of mitochondrial permeability transition.…”
Section: Discussionmentioning
confidence: 99%
“…This has been ubiquitously observed in multiple ischemic insult models such as 5 regional 4 or global ischemia and cardiac arrest 2, 3 . Mitochondrial dysfunction has been 6 mostly investigated during the post-ischemic reperfusion phase 4,5 . Targeting mitochondria is 7 then often considered as a relevant approach to prevent reperfusion injury through, e.g.,…”
mentioning
confidence: 94%
“…, opening of the mitochondrial permeability transition pore (mPTP) 4 and cytochrome c 4 release 1, 2 . This has been ubiquitously observed in multiple ischemic insult models such as 5 regional 4 or global ischemia and cardiac arrest 2, 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Argaud et al were the first to link IPOC with the inhibition of mPTP opening, by demonstrating increased calcium retention in mitochondria isolated from postconditioned in vivo rabbit hearts compared with control hearts. 17 Furthermore, mice lacking mitochondrial cyclophilin D, a presumed regulatory component of the mPTP, are resistant to cardioprotective effects of both IPC and IPOC, 18 confirming the regulatory role of mPTP. More recently, it has been shown that administration of a single bolus of cyclosporin A, an inhibitor of mPTP opening, at the time of reperfusion was associated with a smaller infarct size in patients with AMI.…”
Section: Mitochondria As the End Effectorsmentioning
confidence: 89%